A PENGARUH PUPUK ORGANIK CAIR Leucaena leucocephala L. DAN KULIT PISANG TERHADAP PERTUMBUHAN TANAMAN KAKAO: Kakao, Media Tanam, Organik Cair - Rizka Rahmahwati; Peliyarni; Hasrin; Urmayani, Fifit (Universitas Muslim Buton, 2023)
Cocoa (Theobroma cacao L.) is a plantation commodity with high economic value. The need for cacao is increasing but the production yields are decreasing every year, so it is necessary to increase cocoa production. The purpose of this study was to find out how the application of liquid organic fertilizer can increase the growth of cocoa plants and how to apply liquid organic fertilizer to cocoa plants. The research was carried out in several stages, namely making liquid organic fertilizer and planting cocoa plants. This study used a randomized block design with the Least Significant Difference (LSD) test. The results showed that the application of liquid organic fertilizer to cocoa seedling plants had an effect on growth and gave better results than without the application of liquid organic fertilizer. The highest yield was found in the 500 mL/L treatment with an average plant height of 20.67 cm, leaf area of 28.49 cm and an average number of leaves of 5.67.